2002
DOI: 10.1128/iai.70.3.1185-1192.2002
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gamma Interferon-Induced Major Histocompatibility Complex Class II Gene Expression byPorphyromonas gingivalisMembrane Vesicles

Abstract: Gamma interferon (IFN-␥)-induced endothelial cells actively participate in initiating immune responses by interacting with CD4؉ T cells via class II major histocompatibility complex (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
1
27
0
1
Order By: Relevance
“…Previous reports have shown that MVs possess various virulent abilities (9,13,25,39,40,43,48), while our results indicate a new aspect of cellular function impairment by P. gingivalis MVs.…”
Section: Discussionsupporting
confidence: 63%
“…Previous reports have shown that MVs possess various virulent abilities (9,13,25,39,40,43,48), while our results indicate a new aspect of cellular function impairment by P. gingivalis MVs.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, MVs have been reported to possess various virulent abilities (9,13,21,39,41,47,51). We intend to conduct additional studies to elucidate the cellular functions impaired by invading MVs.…”
Section: Discussionmentioning
confidence: 99%
“…Neisseria vesicles have been proposed to act as decoys to the immune system, binding and removing cell-targeted bactericidal factors in serum (Pettit and Judd 1992). The gingipain proteases on P. gingivalis vesicles cause CD14 degradation on O937 human macrophages that could lead to disarming the responsiveness of the immune system in periodontal disease (Duncan et al 2004) P. gingivalis vesicles also induce membrane expression of E-selectin and ICAM-1 on vascular endothelial cells, whereas they inhibit synthesis of interferon ␥ MHC class II synthesis (Srisatjaluk et al 1999(Srisatjaluk et al , 2002.…”
Section: Modulation Of Host Responsementioning
confidence: 99%